Exploring Congolese refugees' experiences with abortion care in Uganda: a multi-methods qualitative study. Issue 1 (1st January 2019) - Nara, Ruth; Banura, Amanda; Foster, Angel M.
Abstract: Uganda hosts 1.4 million refugees and conflict-affected people. Widely regarded as the best place in Africa to be a refugee, Uganda's policies encourage self-sufficiency and local integration. However, abortion is legally restricted and recent studies suggest that displaced women and girls have persistent unmet sexual and reproductive health needs. In 2017, we conducted a multi-methods study to assess the reproductive health needs of displaced Congolese women in camp- and urban-based settings in Uganda. Our project focused on maternal health and delivery care, contraception, and abortion/post-abortion services and the intersection of these issues with sexual and gender-based violence. We interviewed 11 key informants, facilitated 4 focus group discussions with refugee women, and conducted 21 in-depth interviews with Congolese women of reproductive age to understand better knowledge, attitudes, practices, and services. Using both inductive and deductive techniques, we employed a multi-phased analytic plan to identify content and themes and triangulate and interpret findings. Our results suggest that Congolese refugees in Uganda are unable to navigate the legal restrictions on abortion and are engaging in unsafe abortion practices. This appears to be the case for those living in both camps and urban areas. The legal restrictions on induced abortion pose a barrier to the provision of post-abortion care. Efforts to ensure access to comprehensive abortion care should be prioritised and providing information and support to women in need of post-abortion care is imperative.